Comparing Nonprofit Charter and Traditional Public School Board Member Perceptions of the Public, Conflict, and Financial Responsibility: Is there a difference and does it matter?. Issue 7 (8th August 2016) - Ford, Michael R.; Ihrke, Douglas M.
Abstract: In this paper, survey data collected from nonprofit charter school board and elected public school board members in Minnesota is used to test three hypotheses relating to theories of New Public Management, democratic governance, and small group dynamics. We find that nonprofit charter school board members perceive lower levels of conflict, place less priority on the general public, and perceive a higher degree of governance responsibly in the area of financial management, than elected board members. We conclude that the increased use of nonprofit charter schools has potentially substantial implications on accountability and effectiveness in the delivery of public education.